Fluorine-Free Corrosion-Resistant Electrolyte Design for Enhanced Stability in Lithium Metal Batteries - Jo, Hyeonmin; Lee, Uijun; Kwak, Jin Hwan; Park, Jungjin; Yun, Jiyoung; Kim, Seonju; Lee, Jun-won; Ryu, Hee Seung; Park, Sunjin; Jo, Cheolwoo; Kim, Byunghoon; Lim, Hee-dae (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2026)
Advancing liquid electrolyte design is crucial for overcoming the performance limitations of current battery technologies and enabling next-generation energy storage systems. Among recent developments, localized high-concentration electrolytes (LHCEs) have demonstrated remarkable cycling stability. However, their reliance on fluorinated diluents, which are highly reactive with lithium metal, inevitably leads to severe spontaneous corrosion. This study introduces a fluorine-free, corrosion-resistant diluent (CRD) strategy, employing benzene as the CRD in combination with amphiphilic butyl methyl ether as the primary solvent. This electrolyte design simultaneously extends both cycle and calendar life by promoting an anion-dominated solvation structure, while the diluent effectively suppresses lithium metal corrosion. As a result, the CRD-based electrolyte exhibits outstanding durability and stability compared to conventional LHCEs. Moreover, the fluorine-free and cost-effective electrolyte–diluent system offers strong advantages for practical applications. Overall, this study demonstrates the potential of the CRD strategy to achieve stable electrode–electrolyte interfaces and provides broader insights for diverse battery chemistries.